2022
DOI: 10.1200/jco.2022.40.4_suppl.016
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade alone for mismatch repair deficient (dMMR) locally advanced rectal cancer.

Abstract: 16 Background: Total neoadjuvant therapy with induction chemotherapy and chemoradiation (chemoRT) is the standard treatment for locally advanced rectal adenocarcinomas. Mismatch repair deficient (dMMR) rectal tumors respond poorly to neoadjuvant chemotherapy. PD-1 blockade is effective in patients with metastatic dMMR colorectal cancers, but its efficacy has not been established in the neoadjuvant setting. The purpose of this study is to evaluate the clinical benefit of neoadjuvant PD-1 blockade in dMMR local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Patients with MSI-H/dMMR GAC have had dramatic results with immune checkpoint therapy, as evident with MSI-H/dMMR metastatic colorectal cancer 9 12 . Programmed death-1 blockade is under investigation in localized MSI-H/dMMR solid tumors 13 , 14 . Lumish et al recently reported the results of 12 localized stage II or III MSI-H/dMMR rectal cancer patients who achieved 100% objective response rate (ORR) with dostarlimab, an anti-PD-1 agent 13 .…”
Section: Main Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MSI-H/dMMR GAC have had dramatic results with immune checkpoint therapy, as evident with MSI-H/dMMR metastatic colorectal cancer 9 12 . Programmed death-1 blockade is under investigation in localized MSI-H/dMMR solid tumors 13 , 14 . Lumish et al recently reported the results of 12 localized stage II or III MSI-H/dMMR rectal cancer patients who achieved 100% objective response rate (ORR) with dostarlimab, an anti-PD-1 agent 13 .…”
Section: Main Discussionmentioning
confidence: 99%
“…Programmed death-1 blockade is under investigation in localized MSI-H/dMMR solid tumors 13 , 14 . Lumish et al recently reported the results of 12 localized stage II or III MSI-H/dMMR rectal cancer patients who achieved 100% objective response rate (ORR) with dostarlimab, an anti-PD-1 agent 13 . This phase 2 trial reported on seven patients who completed induction therapy.…”
Section: Main Discussionmentioning
confidence: 99%
“…Future studies might take into consideration biomarkers such as circulating tumor DNA (ctDNA) following NAT that might inform adjuvant strategies in patients with persistent ctDNA after NAT and surgical resection. Alternatively, identifying LARC patients with MSI might warrant an alternative sequence of NAT, CRT followed CT and potentially incorporation of ICIs either alone or in combination with CRT (40). Importantly, the current study highlights the real-world feasibility, e cacy, and safety of this protocol in an LMIC setting with pCR and 2-year DFS rates which are comparable to contemporary studies done in No surgery done represents the patients who were initiated on or completed TNT but did not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent abstract presented at the 2022 ASCO Gastrointestinal Cancers Symposium suggests that most patients with hypermutated tumors achieve a cCR to PD-1 blockade. 96 Although the follow-up is short, the results of this trial are provocative and suggest that most tumors positive for microsatellite instability/hypermutation are candidates for organ preservation.…”
Section: Watch-and-wait Approach In Rectal Cancer: Controversies and ...mentioning
confidence: 94%